PERJANJIAN SIMPAN PINJAM MATA UANG ASING PADA BANK BRI (STUDI KASUS KESALAHAN TRANSFER DANA NASABAH YANG DILAKUKAN BANK BRI) - Azaria Maharani; Gunardi Gunardi (Jurnal Hukum Adigama, 2022)
Banking is an important activity for society. Main role of banking are for storing and distributingfunds. Banking activities must be carried out carefully and professionally so as to minimize false step.If something goes wrong then what should be done based on the existing law. To handle it, thegovernment has made applicable legal regulations, one of which is Law No. 3 of 2011 concerning theTransfer Of Funds. Therefore, this research was made to find out this problem. This study uses anormative method that uses existing laws as the main data and other data as relevant data. The resultof this study is that the party who made a mistake must immediately correct the error and adjust to thetheory used, the Bank is also obliged to compensate for the amount of compensation that is equivalentto the mistake that has been made. When the bank makes a mistake, it is necessary to justify andprovide compensation to the recipient of the funds.